Serological detection of antibodies to Anaplasma spp., Borrelia burgdorferi sensu lato and Ehrlichia canis and of Dirofilaria immitis antigen in dogs from Costa Rica - Montenegro, Víctor M. (2017)
In a study in Costa Rica 314 serum samples from dogs throughout all seven provinces were tested using a commercial kit for the detection of circulating antibodies against Anaplasma spp., Borrelia burgdorferi sensu lato and Ehrlichia canis, and of circulating antigen of Dirofilaria immitis. A total of 6.4% (20/314) and 38.2% (120/314) were positive for Anaplasma spp. (An) and E. canis (Ec) antibodies. Overall, 8.0% (25/314) were positive for D. immitis (Di) antigen. One single dog reacted positive with B. burgdorferi s.l. (Bb) antigen (0.3%, 1/314). E. canis positive dogs were detected in all provinces (highest percentages in Guanacaste, Puntarenas [both significantly different compared to the overall] and Limón). Guanacaste and Puntarenas also showed the highest prevalences of Anaplasma spp. (both significantly different compared to the overall). The highest prevalence of D. immitis was detected in Puntarenas (significantly different compared to the overall). Double pathogen exposure (Ec plus An; Ec plus Di; Ec plus Bb) were recorded in 8.9% (28/314). Two dogs showed a triple pathogen exposure (0.6%, 2/314; An, Ec and Di). There was a significant difference between male (11.5%, 18/156) and female (4.4%, 7/158) animals for D. immitis positive results. There was also a significant difference between breed and no breed dogs regarding the characteristics of a general positive test, as well as seropositivity to the single pathogens of Anaplasma spp., E. canis and D. immitis. Finally there was a significant difference in the presence of clinical signs again regarding the characteristics of a general positive test, as well as seropositivity to Anaplasma spp., E. canis and D. immitis. Practitioners in Costa Rica should be aware of the canine vector-borne diseases mentioned as dogs are at risk of becoming infected. Concerning the positive B. burgdorferi s.l. dog, an autochthonous occurrence cannot be confirmed due to a history of adoption and an unusual tattoo number. Veterinary advice to protect dogs and limit transmission of vector-borne pathogens, also to humans, by using prophylactic measures is strongly recommended.